Characterization of kesterite thin films fabricated by rapid thermal processing of stacked elemental layers using spatially resolved cathodoluminescence - Künecke, Ulrike; Hetzner, Christina; Möckel, Stefan; Yoo, Hye Sun; Hock, Rainer; Wellmann, Peter (Thin Solid Films, 2015)
We report on the microstructure analysis of kesterite (Cu2ZnSnSe4) layers from rapid thermal processing of sequential elemental layers by spatially resolved cathodoluminescence in a scanning electron microscope. Energy dispersive X-ray fluorescence, X-ray diffraction and Raman spectroscopy were carried out for the validation of the findings. Special emphasis is put on the discussion of the occurrence of the secondary phases Cu2SnSe3, Cu2Se, ZnSe and SnSe. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Cu2ZnSnSe4; Cathodoluminescence; Secondary phases; Microstructure